Actuator stiction compensation via variable amplitude pulses. (February 2018) - Arifin, B.M.S.; Munaro, C.J.; Angarita, O.F.B.; Cypriano, M.V.G.; Shah, S.L.
Abstract: A novel model free stiction compensation scheme is developed which eliminates the oscillations and also reduces valve movement, allowing good setpoint tracking and disturbance rejection. Pulses with varying amplitude are added to the controller output to overcome stiction and when the error becomes smaller than a specified limit, the compensation ceases and remains in a standby mode. The compensation re-starts as soon as the error exceeds the user specified threshold. The ability to cope with uncertainty in friction is a feature achieved by the use of pulses of varying amplitude. The algorithm has been evaluated via simulation and by application on an industrial DCS system interfaced to a pilot scale process with features identical to those found in industry including a valve positioner. Highlights: A stiction compensation method with pulses of variable amplitude is proposed. Fewer parameters are required for implementation while comparing with other methods in literature. The algorithm was evaluated via simulations and implementation on an industrial distributed control system. The ability to cope with uncertainty in friction and sequential setpoint changes.